Integrated tree-ring-radiocarbon high-resolution timeframe to resolve earlier second millennium BCE Mesopotamian chronology - Manning, Sturt W.; Griggs, Carol B.; Lorentzen, Brita; Barjamovic, Gojko; Ramsey, Christopher Bronk; Kromer, Bernd; Wild, Eva Maria (PLOS ONE, 2016)
500 years of ancient Near Eastern history from the earlier second millennium BCE, including such pivotal figures as Hammurabi of Babylon, Šamši-Adad I (who conquered Aššur) and Zimrilim of Mari, has long floated in calendar time subject to rival chronological schemes up to 150+ years apart. Texts preserved on clay tablets provide much information, including some astronomical references, but despite 100+ years of scholarly effort, chronological resolution has proved impossible. Documents linked with specific Assyrian officials and rulers have been found and associated with archaeological wood samples at Kültepe and Acemhöyük in Turkey, and offer the potential to resolve this long-running problem. Here we show that previous work using tree-ring dating to place these timbers in absolute time has fundamental problems with key dendrochronological crossdates due to small sample numbers in overlapping years and insufficient critical assessment. To address, we have integrated secure dendrochronological sequences directly with radiocarbon (14C) measurements to achieve tightly resolved absolute (calendar) chronological associations and identify the secure links of this tree-ring chronology with the archaeological-historical evidence. The revised tree-ring-sequenced 14C time-series for Kültepe and Acemhöyük is compatible only with the so-called Middle Chronology and not with the rival High, Low or New Chronologies. This finding provides a robust resolution to a century of uncertainty in Mesopotamian chronology and scholarship, and a secure basis for construction of a coherent timeframe and history across the Near East and East Mediterranean in the earlier second millennium BCE. Our re-dating also affects an unusual tree-ring growth anomaly in wood from Porsuk, Turkey, previously tentatively associated with the Minoan eruption of the Santorini volcano. This tree-ring growth anomaly is now directly dated ~1681-1673 BCE (68.2% highest posterior density range), ~20 years earlier than previous assessments, indicating that it likely has no association with the subsequent Santorini volcanic eruption.
Gesehen am 07.05.2020